2012
DOI: 10.1002/bjs.8836
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative management of acute cholecystitis in the elderly

Abstract: Despite selection of the best elderly candidates for cholecystectomy, postoperative morbidity was significant. Medical management, with interval cholecystectomy only for recurrent AC, may be appropriate in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
76
5
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 30 publications
8
76
5
4
Order By: Relevance
“…25 The rate of complications following LC in the elderly is estimated to be 22%. 5,7,9,[26][27][28] In the present study, a similar rate of major morbidity was observed (23%) to the rates reported for other series of patients undergoing interval cholecystectomy after PCY (Table 4). [2][3][4][5][6][7][8][9]29 Routine drainage at cholecystectomy did not prevent abscess formation in five patients.…”
Section: Surgical Techniquesupporting
confidence: 89%
“…25 The rate of complications following LC in the elderly is estimated to be 22%. 5,7,9,[26][27][28] In the present study, a similar rate of major morbidity was observed (23%) to the rates reported for other series of patients undergoing interval cholecystectomy after PCY (Table 4). [2][3][4][5][6][7][8][9]29 Routine drainage at cholecystectomy did not prevent abscess formation in five patients.…”
Section: Surgical Techniquesupporting
confidence: 89%
“…Many authors confirm the safety and effectiveness of cholecystostomy for the initial treatment (7,8,9). Proper patient selection is important in the ACC group to reduce the risk of recurrence and to avoid urgent cholecystectomy (11,14,16). There are many controversies in the current literature.…”
Section: Resultsmentioning
confidence: 99%
“…16 In certain cases, PC may be the definitive treatment if the patient is not a surgical candidate even after the acute event. 17 In other cases, patients may be considered for a cholecystectomy after the acute septic episode has resolved. However, there remains no consensus in selecting these patients for either group.…”
mentioning
confidence: 99%
“…There are studies that have reviewed outcomes in elderly patients undergoing a cholecystectomy 17,18 but there are few studies that have reviewed outcomes for elderly patients treated conservatively. In particular, there are sparse data on the rate of recurrent AC in elderly patients.…”
mentioning
confidence: 99%